P124 Gastroenteropancreatic Neuroendocrine Neoplasms in patients with Inflammatory Bowel Disease: An ECCO CONFER Multicentre Case Series. (27th May 2021) - Festa, S; Zerboni, G; Derikx, L; Ribaldone, D G; Dragoni, G; Buskens, C J; Nieveen van Dijkum, E; Pugliese, D; Panzuto, F; Krela-Kaźmierczak, I; Reiss, H; Shitrit, A B G; et al.
Abstract: Background: Neuroendocrine Neoplasms (NENs) are a heterogeneous group of tumours deriving from the diffuse endocrine system. NENs may occur almost everywhere in the body but are most common in the gastrointestinal tract, the pancreas, and the lungs, with gastroenteropancreatic (GEP) tumours representing 70% of all NENs. GEP-NENs have rarely been reported in association with inflammatory bowel diseases (IBDs) but no definitive relationship between these tumours and IBD has been established Methods: This was an ECCO COllaborative Network For Exceptionally Rare case reports project (ECCO-CONFER). We included cases of GEP-NENs diagnosed in patients with IBD that met the diagnostic criteria for NEN according to the European Neuroendocrine Tumour Society. Data were retrospectively collected in a standardized case report form and analysed for event association with patient's and IBD-related factors Results: GEP-NEN was diagnosed in 100 patients with IBD [61% female, 55% Crohn's disease, median age 48 years (IQR 37–59)]. Overall the most common location was the appendix (39/100) followed by the colon (22/100). Complete IBD-related data was available for 50 individuals with a median follow-up of 30.5 months (IQR 11.2–70) following NEN diagnosis. At the last follow-up data, 47/50 patients were alive. Three deaths occurred, of which 2 were related to NEN. Median duration of IBD at NEN diagnosis was 84 months (IQR 10–151), and in 18% of cases NEN and IBD were diagnosed concomitantly. 20/50 of NENs were at stage I (T1N0M0) and 28/50 graded G1 (ki 67 ≤2 %) at diagnosis. Incidental diagnosis of NEN either during follow-up or during surgery as well as receiving diagnosis of NEN concomitantly with IBD was significantly associated with an earlier NEN stage (p< 0.01 and p<0.02, respectively). Exposure to immunomodulatory and/or biologic therapy was not associated with advanced NEN stage or grade. Interestingly, primary GEP-NEN sites significantly correlated to the segment affected by IBD (62% vs 38% p = 0.02) Conclusion: In the largest case series to date, prognosis of patients with concomitant GEP-NEN and IBD seems favorable. Incidental NEN diagnosis correlates with an earlier NEN stage and IBD-related therapies are independent of NEN stage and grade. The association of GEP-NEN location and the segment affected by IBD may suggest a possible role of inflammation in NEN tumorigenesis